PELATIHAN BISNIS MELALUI PEMANFAATAN MEDIA SOSIAL INSTAGRAM PADA KALANGAN IBU- IBU PKK RW 01 PONDOK LABU - Roosita Cindrakasih; Cindya Yunita Pratiwi; Riastri Novianita; Debby Andra Fortuna; Vika Yustia; Reva Widyanti (Yayasan Education and Social Center, 2021)
Training for some people is to add skills (ability) to do something. Of course it provides knowledge and experience that is increasing. UBSI and PKK RW.01, Pondok Labu women synergize together to carry out activities that begin with a passion to provide education in terms of the use of social media in this case is Instagram. In the academic world, community-based activities are packaged with the term Community Service. Community involvement is a clear and consistent existence of every university to carry out the Tri Dharma. The choice of a theme that is adapted to the linear discipline of the UBSI Campus is an absolute must, as a form of professionalism and proportion in doing community service. Business training is the central issue of this training, because many PKK women currently use social media to market the products/services they sell. This is a good form of cooperation, because theory and practice are tried to be combined. The selection of PKK women in RW 01 Pondok Labu, because many of the mothers here use Instagram to do business even though it is still relatively new in its application. However, this gives a signal that these mothers have a great interest and willingness to learn and do business. This challenge is the priority of our team to make this object a community service which of course is relevant to our academic studies.